Women’s mountaineering and dissonances within the mountain guide profession - Rozenn Martinoia (Revue de Géographie Alpine)
The mountains are a place for economic activity and work for the guides and a place for fun and recreation for their clients. For each of them, however, the mountains remain a space for social relations, which are woven onto a canvas of representations and pre-existent social relationships, including gender. This article focuses on the ambivalent role of the female clientele in the construction of the gendered professional identity of male mountain guides and its validation by peers. Within a profession normed by a myth of masculinity, female clients may indeed send out dissonant signals: on the one hand, they allow the production of expected signs of masculinity, on the other, they may symbolise a feminisation of professional skills, which, in the hierarchy of gender, is stigmatising. In this respect, the guides negotiate a compromise by manoeuvring between the multiple axiological frameworks, which construct and validate both their gender and professional identities. Supported by an ethnographic survey, this article particularly highlights the prominence of the masculine guide myth which norms interactions within the professional group. It shows why and how guides, essentially by means of discursive artifice, save face in front of their peers.